INOVASI DUKCAPIL DIGI MOBIL DALAM MENINGKATKAN PELAYANAN PUBLIK PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PARIAMAN - Dahlila Dahlila; Aldri Frinaldi (Journal of Education on Social Science (JESS), 2020)
Progress in information technology today also modernize various public services including population registration services. Nowadays people always wanted services that were easier and did not need to queue at service counters. To minimize problems related to services, public service providers make innovations in service. The Department of Population and Civil Registration of Pariaman City as the organizer of population document management services has made an internet-based innovation called Dukcapil Digi Mobile which means being served geniusly. By using qualitative research methods and data collection techniques carried out by interviews, observation, and documentation study, the results of this study showed that the Dukcapil Digi Mobile innovation criteria were successful in terms of the success factors in implementing the innovation. Its implementation was influenced by supporting and inhibiting factors.